2008
DOI: 10.1037/1045-3830.23.2.187
|View full text |Cite
|
Sign up to set email alerts
|

Effects of general and broad cognitive abilities on mathematics achievement.

Abstract: This study investigated the direct and indirect effects of general intelligence and 7 broad cognitive abilities on mathematics achievement. Structural equation modeling was used to investigate the simultaneous effects of both general and broad cognitive abilities on students' mathematics achievement. A hierarchical model of intelligence derived from the Cattell-Horn-Carroll (CHC) taxonomy of intelligence was used for all analyses. The participants consisted of 4 age-differentiated subsamples (ranging from ages… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
120
1
8

Year Published

2010
2010
2018
2018

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 173 publications
(149 citation statements)
references
References 41 publications
16
120
1
8
Order By: Relevance
“…Our results are in line with other studies that show the major role of non-verbal intelligence in academic performance for various subjects [1,15]. Moreover, intelligence plays a central role in the relationship between cognitive functions and academic performance [2].…”
Section: Regression Analysessupporting
confidence: 83%
“…Our results are in line with other studies that show the major role of non-verbal intelligence in academic performance for various subjects [1,15]. Moreover, intelligence plays a central role in the relationship between cognitive functions and academic performance [2].…”
Section: Regression Analysessupporting
confidence: 83%
“…There is strong evidence for a more general correlation between these skills. Several studies involving broad batteries of cognitive ability found relational reasoning to be strongly correlated with mathematics performance, above effects of other cognitive factors [17], and across various age ranges [18,19]. These data are strengthened by recent longitudinal analyses that indicate a developmental link between reasoning skills and math achievement.…”
Section: Evidence Of Correlation Between Reasoning and Mathematicssupporting
confidence: 54%
“…Second, the interactions of complex medication routines and strict dialysis cycles may decrease attentional control, working memory, and executive function, cognitive domains that are important to children's ability to acquire, understand, and retain information in social and educational environments (37,39,40). In particular, lower mathematic scores may be attributed to the reduced overall neurocognitive function of children with CKD, with fluid reasoning and processing speed having direct and indirect effects on mathematic ability (41,42). Studies examining the relationship between intelligence (full-scale IQ) and academic performance reported a moderate and statistically significant correlation moderated by factors, such as attendance, motivation, home and school environments, and cultural demographics (3,43).…”
Section: Discussionmentioning
confidence: 99%